1981
DOI: 10.1139/v81-329
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 nmr shifts and C—H coupling constants of deoxybenzoins and related acetophenones

Abstract: 13C Chemical shifts and resolved carbon–proton couplings of 39 deoxybenzoins and 11 acetophenones, most of which have naturally occurring substitution patterns, are assigned. Individual benzene rings turned out to have typical parameters not affected by structural variations in the rest of the molecule. Due to substitutional saturation, however, these benzenoid carbon shifts markedly deviate from increment additivity. A few trends of these deviations are described. Phenolic hydrogens, fixed between hydroxyl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Engl. Ochnaceae lead to the identification of the triterpenes friedelin (1) (Mahato & Kundu, 1994) and 3β-friedelinol (2) (Salazar et al, 2000), the isoflavone 4',5,7-trimethoxyisoflavone (3) (Jha et al, 1980;Wang, 2005) and the flavone 4',5-dihydroxy-3',5',7-trimethoxyflavone (4) (Zahir et al, 1996) and two glycosides 5 and 6 identified sitosteryl and stigmasteryl 3-O-β-D-glucopyranosides (Chaurasia & Wichth, 1987) …”
Section: Resultsmentioning
confidence: 99%
“…Engl. Ochnaceae lead to the identification of the triterpenes friedelin (1) (Mahato & Kundu, 1994) and 3β-friedelinol (2) (Salazar et al, 2000), the isoflavone 4',5,7-trimethoxyisoflavone (3) (Jha et al, 1980;Wang, 2005) and the flavone 4',5-dihydroxy-3',5',7-trimethoxyflavone (4) (Zahir et al, 1996) and two glycosides 5 and 6 identified sitosteryl and stigmasteryl 3-O-β-D-glucopyranosides (Chaurasia & Wichth, 1987) …”
Section: Resultsmentioning
confidence: 99%
“…The substitution patterns presented can be classified into 2,4-dioxygenated (1-7), 3,4-dioxygenated (8, 9), 2,5dioxygenated (10), 2,3,4-trioxygenated (11)(12)(13)(14)(15)(16), 2,4,5-trioxygenated (17)(18)(19)(20), and 2,4,6-trioxygenated (21)(22)(23)(24)(25) series of DOBs with various rings B. DOB 13 was found to be a new compound, and the NMR spectral data of 24 (29) were the first presented. DOBs 1, 3, and 4 were synthesized by W€ ah€ al€ a et al (20), and the data of 5 and 18 were reported previously in a NMR spectral study by Jha et al (30) (20).…”
Section: Methodsmentioning
confidence: 99%
“…1.41 g, 52%; R f = 0.40 (EtOAc/acetone/ n -hexane = 2:0.5:7.5); colorless needles (MeOH), mp 110 °C; 1 H NMR (CDCl 3 , 400 MHz, 25 °C) δ 3.79, 3.83 (each 3H, s, OMe), 4.15 (2H, s, CH 2 ), 6.42 (1H, d, J = 2.4 Hz, H-3), 6.44 (1H, dd, J = 2.4, 8.8 Hz, H-5), 6.88 (2H, d, J = 8.8 Hz, H-3′,5′), 7.19 (2H, d, J = 8.8 Hz, H-2′,6′), 7.75 (1H, d, J = 8.8 Hz, H-6), 12.74 (1H, s, C-2 OH); 13 C NMR (CDCl 3 , 100 MHz, 25 °C) δ 43.9 (CH 2 ), 55.3 (OMe), 55.5 (OMe), 101.0 (C-3), 107.8 (C-5), 113.1 (C-1), 114.2 (C-3′,5′), 126.3 (C-1′), 130.3 (C-2′,6′), 132.0 (C-6), 158.7 (C-4′), 165.8 (C-4), 166.1 (C-2), 202.3 (CO); EI-MS m / z 272 [M] + , 151 .…”
Section: Methodsmentioning
confidence: 99%